Pengaruh Kompetensi Sosial Guru Terhadap Keterlibatan Ayah di PAUD Talenta - Bani, Mersi; Sartika Kale; Angelikus N. Koten; Gokma N. Tampubolon (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Professional teachers have social competence that can influence fathers' engagement in schools, so that such engagement can support parenting in shaping children's character and morals. The purpose of this study is to see if there is an influence of teachers' social competence on fathers' involvement in children's education at school. The research method is quantitative with data collection techniques used is a questionnaire. Informants in this study were representatives of 15 fathers of children attending Talenta PAUD. The results of the study through statistical testing of questionnaire data on the influence of teachers' social competence on fathers' engagement showed a simple linear regression equation which showed a significance value of 0.000 (<0,05), so the alternative hypothesis (Ha) is accepted. Teachers' social competence contributes 64.8% to fathers' engagement in early childhood education, while the rest is influenced by factors outside the study. It can be concluded that the variable of teachers' social competence has an influence on the variable of fathers' engagement at Talenta PAUD.